The Relationship Between Hardiness And Career Adaptability Of Vocational Students - Hadi, Abdul; Aryani, Eka; Nurbaiti, Anifa Tuzzuhroh (Universitas Islam Bunga Bangsa Cirebon, 2024)
Vocational education is education that prepares students to be able to work in certain situations in certain fields. In line with the goals of vocational education, it places more emphasis on practice, especially career adaptability. However, there are several obstacles related to this ability, including: students do not understand future career decisions, lack confidence in making job decisions according to their talents, one of which is related to career adaptability. This research is correlational research regarding the relationship between hardiness abilities and vocational school students' career adaptability abilities. The sample in the research was simple random sampling, totaling 40 vocational school students. The data collection instrument used the hardiness and career adaptability scale instruments. The research results show that the correlation test between hardiness (X) and career adaptability (Y) is 0.912 with sig. = 0.000 (p<0.01). In conclusion, there is a significant relationship between these two variables. This can be seen in the aspects of control, commitment and challenge. In line with these results, it means that the higher the student's hardiness, the higher their career adaptability will also be. Apart from that, career adaptability and hardiness are able to make individuals develop and control the situations they face.